Actor or ally? Exploring Sweden’s involvement in Turkish gender politics through the Swedish Consulate General in Istanbul - Fregert Tolgraven,Maja (2020)
The aim of this project is to study the implementation of Sweden’s feminist foreign policy through its gender equality enchancing foreign aid to Turkish civil society, managed by The Swedish Consulate General in Istanbul. Through a multi-methods study based on document analysis of project grant cases in 2019, and in-depth interviews with Consulate staff and representatives from partner organizations, the study maps a web of different actors and processes of change in Turkish gender politics: states, civil society, segments of the public and the international community. Using the theoretical framework of feminist international relations regarding the role of the state and the global gender equality regime, in dialogue with postcolonial critique of Western involvement in the name of feminism, the study discusses the role of Sweden balancing practices of missionary feminism and alliances of solidarity. In between a frozen EU accession process and an authoritarian Turkish state, the study concludes that the Swedish efforts continue to have an impact through their support to democratic and feminist forces in civil society who manage to create and sustain progressive undercurrents for gender equality that challenge the repressive and conservative political climate.
Keywords: gender equality; feminist foreign policy; civil society; Turkey; EU accession